ANALISIS KONSEPTUAL PENGGUNAAN SELF-TALK MOTIVASIONAL DALAM PENDIDIKAN JASMANI DI SMAN 1 PARUNG - Sidqi, Fahmi Khairu; Paramitha, Sandey Tantra (Jurnal Sains Riset, 2024)
The aim of this research is to analyze motivational self-talk from these three indicators, namely self-confidence indicators, expressions of strength and anxiety control that are most trusted by class X students at SMAN 1 Parung to increase enthusiasm for learning. This research uses a quantitative descriptive method with a questionnaire distribution technique. The population of this research was class X students at State Senior High School (SMAN) 1 Parung, totaling 377 students. By taking samples using random sampling techniques, the required number of research samples was 79 students. The instrument used in this research was a self-talk questionnaire received from a journal entitled "Automatic Self-Talk Questionnaire for Sports (ASTQS)" by (Zourbanos, Hatzigeorgiadis, Chroni, Theodorakis, Papaioannou, 2009. Data analysis techniques used in the research This is a descriptive analysis using Respondent Achievement Level (TCR) to find out which indicator gets the highest points in the data. Based on the results of data analysis and processing, the self-confidence indicator from the 5 statement items after analysis has a respondent achievement level (TCR) of 87. 44 and is in the "very good" (SB) category. This result is the highest score and it can be concluded that the self-confidence indicator is the indicator that is most trusted to increase students' enthusiasm for learning